DIVERSITY, HOST- AND HABITAT- PREFERENCES ON THE FUNGI COMMUNITIES FROM THE ROOTS OF CYMBIDIUM SPP. AT TWO SITES IN CHINA - F. Huang; C. Y. Zhang (Journal of Animal and Plant Sciences, 2015)
Three species of Cymbidium spp., Cymbidium faberi, Cymbidium goeringii, and Cymbidium goeringii var. longibracteatum were collected from two different habitats in southwestern China, including a subtropical forest and a transplanted site nearby. Two hundred and ninety isolates, obtained from the roots of the three orchids, were characterized through both morphological and molecular methods. Among a total of 32 taxa, 8 were classified to the level of species and the other 24 to genus. One comprising 205 isolates belonged to ascomycetes (69%), another of 48 basidiomycetes (16%), and the last of 43 belonged to zygomycetes (15%). This revealed high taxonomic diversity in fungal composition, including typical orchid mycorrhiza of the Tulasnella and several other endophytic fungi of the Pezizales and Helotiales. The compositions of the fungal communities correlated with host identify or preference. Because of their relatively closer phylogenetic distance, the fungi communities between Cymbidium goeringii and Cymbidium goeringii var. longibracteatum shared more taxa than any others, whether the comparisons were within wild plants or transplants. Two different regions significantly affected the root-associated fungi assemblages. Besides the predominant one, the overlap, even between the common hosts at two sites, shared extremely limited taxa. Orchids of Cymbidium spp. from the wild habitat had a higher number and taxa of root-associated fungi besides the Tulasnella sp. than the transplanted orchids. For the purpose of propagation and conservation, both the host species and the spatial structure of orchids deserve attention as important factors influencing the compositions of fungal communities. It might be important to pay attention to mycorrhizal associations when transplanting orchids of Cymbidium spp. from the wild habitats.
Keywords: Cymbidium spp.; Orchid mycorrhizal fungi; Tulasnella; Diversity; ITS sequences